2020
DOI: 10.1021/acs.est.0c00157
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Biomagnification Capability of Arctic Wolf and Domestic Dog by Equilibrium Sampling

Abstract: The mechanism underlying contaminant biomagnification is a decrease in the volume (V) and the fugacity capacity (Z) of food during digestion in the gastrointestinal tract. Traditionally, biomagnification is quantified by measuring contaminant concentrations in animal tissues. Here, we present a proof-of-concept study to noninvasively derive the thermodynamic limit to an organism’s biomagnification capability (biomagnification limit BMFlim) by determining the ratio of the V·Z-products of undigested and digeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…However, the ϕ NLOM in bear feces had a value (22%) similar to that of the previously measured ϕ NLOM in adult dog feces (20%), even though it was still much lower than that in juvenile dog (40%) and wolf feces (75%). 2 Obviously, the carbon content alone cannot fully explain the ϕ NLOM value in a fecal sample, and the characterization of NLOM is crucial. The low ϕ NLOM in both polar bear and adult dog feces might be due to a large portion of indigestible fibers with a low absorptive capacity for HOCs, e.g., from fresh fruit (e.g., apple) and vegetables (e.g., potato).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the ϕ NLOM in bear feces had a value (22%) similar to that of the previously measured ϕ NLOM in adult dog feces (20%), even though it was still much lower than that in juvenile dog (40%) and wolf feces (75%). 2 Obviously, the carbon content alone cannot fully explain the ϕ NLOM value in a fecal sample, and the characterization of NLOM is crucial. The low ϕ NLOM in both polar bear and adult dog feces might be due to a large portion of indigestible fibers with a low absorptive capacity for HOCs, e.g., from fresh fruit (e.g., apple) and vegetables (e.g., potato).…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the BMF lim value is dependent on both the dietary composition (e.g., lipid content, P lipids ) and the digestion efficiency of a canine. 2 The actual BMF may exceed the BMF lim , if a chemical is more efficiently absorbed from the intestine than it is lost to the intestine: e.g., as a result of the “fat flush” 9 effect or micelle-mediated transport. 10 The BMF lim value can also exceed the BMF value, if processes other than fecal elimination notably contribute to the loss of a chemical from the organism.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations